Development of Three‐Dimensional Completion of Complex Objects. (14th May 2012) - Soska, Kasey C.; Johnson, Scott P.
<x xml:space="preserve">Abstract</x> Three‐dimensional (3D) object completion, the ability to perceive the backs of objects seen from a single viewpoint, emerges at around 6 months of age. Yet, only relatively simple 3D objects have been used in assessing its development. This study examined infants' 3D object completion when presented with more complex stimuli. Infants (N = 48) were habituated to an "L"‐shaped object shown from a limited viewpoint; then they were tested with volumetrically complete (solid) and incomplete (hollow) versions of the object. Four‐month‐olds and 6‐month‐old girls had no preference for either display. Six‐month‐old boys and both sexes at 9.5 months of age showed a novelty preference for the incomplete object. A control group (N = 48), only shown the test displays, had no spontaneous preference. Perceptual completion of complex 3D objects requires infants to integrate multiple, local object features and thus may tax their nascent attentional skills. Infants might use mental rotation to supplement performance, giving an advantage to young boys. Examining the development of perceptual completion of more complex 3D objects reveals distinct mechanisms for the acquisition and refinement of 3D object completion in infancy.